Effect of MgO and Al2O3 precursors on 3D-printed cordierite lattice structures by a novel emulsion-based PDC route - Diamanti, Valeria; Elsayed, Hamada; Fey, Tobias; Bernardo, Enrico (Journal of the American Ceramic Society, 2025)
The development of advanced ceramic materials with tailored microstructures is essential for meeting the demands of many high-performance applications. This study explores a novel polymer-derived ceramic route for fabricating porous cordierite lattice structures by using a silicone-based emulsion as feedstock for direct ink writing. In this context, silicone blended with acrylates enabled the application of a hybrid technology, involving UV curing of the samples after 3D printing to stabilize shapes before high-temperature ceramization. The ceramic product of the silicone-based blend was engineered by emulsification of an aqueous phase, in turn suspending oxide nanoparticles and/or dissolving hydrated salts, acting as Al2O3 and MgO precursors. Several combinations of Al2O3 and MgO precursors were explored to highlight the versatility of the method in yielding cordierite ceramics. Finally, porous structures derived from the combination of hydrated salts were further characterized to investigate the morphology and microstructure of the produced samples, as well as the role of water in the formation of porous components.
CRIS-Team Scopus Importer:2025-07-04
Keywords: cordierite; microemulsion; polymer precursor; printing